Chaotic Attractor Generation via a Simple Linear Time-Varying System - Baiyu Ou; Desheng Liu (Discrete Dynamics in Nature and Society)
A novel generation method of chaotic attractor is introduced in this paper. The underlying mechanism involves a simple three-dimensional time-varying system with simple time functions as control inputs. Moreover, it is demonstrated by simulation that various attractor patterns are generated conveniently by adjusting suitable system parameters. The largest Lyapunov exponent of the system has been obtained.